2009
DOI: 10.1213/ane.0b013e3181aa3063
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Intubations and Mortality: A Level 1 Trauma Center Perspective

Abstract: This prospective study showed a 31% incidence of failed PHI in a large metropolitan trauma center. We found no difference in mortality between patients who were properly intubated and those who were not, supporting the use of bag-valve-mask as an adequate method of airway management for critically ill trauma patients in whom intubation cannot be achieved promptly in the prehospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(96 citation statements)
references
References 26 publications
3
80
0
11
Order By: Relevance
“…This situation can arise independent of location (pre-or in-hospital setting), [1][2][3] clinical expertise (medical technician, nurse, or physician), 4,5 or specialty (emergency medicine, anesthesiology, critical care medicine, or surgery). [6][7][8] The most recent American Society of Anesthesiologists' (ASA) "Practice Guidelines for Management of the Difficult Airway" designate surgical or percutaneous airway, jet ventilation, or retrograde intubation as invasive airway access procedures to secure the airway in both non-emergency and emergency situations.…”
Section: Résumémentioning
confidence: 99%
“…This situation can arise independent of location (pre-or in-hospital setting), [1][2][3] clinical expertise (medical technician, nurse, or physician), 4,5 or specialty (emergency medicine, anesthesiology, critical care medicine, or surgery). [6][7][8] The most recent American Society of Anesthesiologists' (ASA) "Practice Guidelines for Management of the Difficult Airway" designate surgical or percutaneous airway, jet ventilation, or retrograde intubation as invasive airway access procedures to secure the airway in both non-emergency and emergency situations.…”
Section: Résumémentioning
confidence: 99%
“…Our study revealed that four of 554 trauma patients (0.72%) received ESA in emergency surgery settings (odds ratio: 28.9-144.1). In the field of emergency medicine, studies have found that 0.3-0.9% of trauma patients received CTY in pre-hospital or ER settings [3][4][5][6]. Severe facial injury patients received ESA more often than did patients with other types of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…ALS providers need repeated exposure to advanced interventions to maintain their skills [3]. Skill dilution has been an observed phenomenon in models with higher paramedic to population ratio, and some studies have shown a correlation between a smaller number of paramedics to BLS responders, and successful intubation rates [3][4][5][6].…”
Section: Ems Trainingmentioning
confidence: 99%